Retention in care and factors critical for effectively implementing antiretroviral adherence clubs in a rural district in South Africa. Issue 10 (6th October 2019) - Bock, Peter; Gunst, Colette; Maschilla, Leonard; Holtman, Rory; Grobbelaar, Nelis; Wademan, Dillon; Dunbar, Rory; Fatti, Geoffrey; Kruger, James; Ford, Nathan; Hoddinott, Graeme; Meehan, Sue‐Ann
Abstract: Introduction: Differentiated models of care that include referral of antiretroviral treatment (ART) clients to adherence clubs are an important strategy to help clinics manage increased number of clients living with HIV in resource‐constrained settings. This study reported on (i) clinical outcomes among ART clients attending community‐based adherence clubs and (ii) experiences of adherence clubs and perceptions of factors key to successful adherence club implementation among clients and healthcare workers. Methods: A retrospective cohort analysis of routine data and a descriptive analysis of data collected through self‐administered surveys completed by clients and healthcare workers were completed. Clients starting ART at the study clinic, between January 2014 and December 2015, were included in the cohort analysis and followed up until December 2016. The survey data were collected from August to September 2017. The primary outcome for the cohort analysis was a comparison of loss to follow‐up (LTFU) between clients staying in clinic care and those referred to adherence clubs. Survey data reported on client experiences of and healthcare worker perceptions of adherence club care. Results: Cohort analysis reported on 465 participants, median baseline CD4 count 374 (IQR: 234 to 532) cells/μl and median follow‐up time 20.7 (IQR 14.1 to 27.7) months. Overall, 202 (43.4%) participants were referred to an adherence club. LTFU was lower in those attending an adherence club (aHR =0.25, 95% CI: 0.11 to 0.56). This finding was confirmed on analysis restricted to those eligible for adherence club referral (aHR =0.28, 95% CI: 0.12 to 0.65). Factors highlighted as associated with successful adherence club implementation included: (i) referral of stable clients to the club, (ii) an ideal club size of ≥20 members, (iii) club services led by a counsellor (iv) using churches or community halls as venues (v) effective communication between all parties, and (vi) timely delivery of prepacked medication. Conclusions: This study showed good clinical outcomes, positive patient experiences and healthcare worker perceptions of the adherence club model. Factors associated with successful adherence club implementation, highlighted in this study, can be used to guide implementers in the scale‐up of adherence club services across varied high‐burden settings.